Waqf land and sukuk framework for waste disposal management – a conceptual study - Mohd Thas Thaker, Mohamed Asmy; Amin, Md Fouad; Mohd Thas Thaker, Hassanudin; Khaliq, Ahmad; Allah Pitchay, Anwar; Fauziyyah, Neneng Ela; Imon, Riasat Amin (Universiti Malaysia Sabah, 2022)
This paper proposes a viable alternative model for waste management, termed the Waqf Land-Linked Blue Sukuk (WLLBS) model. Owing to its ever-increasing amounts of waste, this paper specifically addresses waste- management in the Indonesian context, specifically, bioplastic production to reduce waste-generation. As this paper focuses on the conceptual development of the WLLBS model, it employs a qualitative content-analysis methodology. In addition to analyzing the literature pertaining to waste-management in Indonesia, this study examines existing studies on the integration of Waqf (Islamic endowment) and Sukuk mechanisms to construct the WLLBS as a funding model. The research identifies environment-friendly bioplastic production using seaweed, as a viable means to significantly reduce the total waste-volume. However, this initiative requires tremendous financial support. In order to address this issue, an innovative Islamic financial mechanism involving the integration of Sukuk and Waqf, is proposed. Similar to the successes of green Sukuk in reducing global carbon emissions (SDG 14), it is hoped that blue Sukuk will similarly address the funding gap to sustain a large-scale seaweed-based bioplastic project in Indonesia. The development of the WLLBS model has huge implications on sustainable development as it reduces the national pollution footprint, furthers the national environmental protection agenda, and eases the government fiscal and debt burdens. These also impact human welfare in terms of quality of living and health. Furthermore, the development of the WLLBS has positive implications on Islamic financial innovation as variations of this model could be adapted to sustainably financing other social-development-related issues.